Evaluation of practices and attitudes of caregivers influencing adherence to seasonal malaria chemoprevention in children under five years of age: the case of Rural Embangweni, Mzimba District, Malawi - Chisomo Salangwa; Reston Munthali; Lusungu Mfune; Vegha Kaunga Nyirenda (Academia Medicine)
This research aimed to investigate medication adherence to seasonal malaria chemoprevention (SMC) and to evaluate the caregivers’ behaviors and attitudes throughout the 2022 SMC campaign in Embangweni, Mzimba District. SMC aims to administer a three-day course of anti-malarial drugs periodically during the months when malaria risk is highest. However, SMC’s effectiveness relies on medication adherence, without which morbidity cannot be reduced. In this study, a random cluster sampling approach was employed to extract data from internal monitoring, with caregivers’ self-reports as the primary information. The caregivers’ adherence levels, beliefs, and behaviors were then assessed and analyzed using Bernard Vrijens’ taxonomy. In total, 95% of caregivers (n = 2,457) were knowledgeable about using drugs to prevent malaria at the outset of treatment when 93.0% of children (n = 2,299) received their initial dose. However, only 66% of caregivers (n = 2,457) indicated that the community health workers supervised the treatment directly. At the beginning of the treatment phase, 89.4% of the children (n = 2,127) took their medication on the second day and 80.2% (n = 2,295) took their medication on the third day. Caregivers cited “forgetting”, “lack of time”, and “absence of the mother” as the primary reasons for halting the three-day prescription. The results of this research indicated that caregivers demonstrated a high level of adherence in completing the entire three-day course of medication and ensuring SMC coverage. However, the survey also highlighted areas of improvement in some caregivers’ attitudes, practices, and knowledge concerning adherence to medication throughout the SMC initiative.